Determinants of capital structure for firms in an Islamic equity index: Comparing developed and developing countries - Evrim Hilal Kahya; Hüseyin Yiğit Ersen; Cumhur Ekinci; Oktay Taş; Koray D. Simsek (Journal of Capital Markets Studies (JCMS), 2020)
Purpose The paper aims to identify the differences between developed and developing country firms with respect to firm-specific and country-level determinants of their capital structure. For this purpose, all constituent firms in one of the oldest Islamic equity indices, Dow Jones Islamic Market World Index (DJIM), are considered and the Muslim-majority status of each firm's domicile country is recognized. Design/methodology/approach The study employs Hausman-Taylor random effects regression with endogenous covariates to explain the debt ratios of firms in DJIM by separating them into developed and developing country subsamples in an unbalanced panel data setting. Developing country subsample is further split into two based on the Muslim-majority status of each firm's domicile country. Findings Consistent with the previous literature, this study finds that firm-specific characteristics are the main determinants of their capital structure. Additionally, the paper shows that country-level characteristics have an impact on the debt ratio, however, the types of factors vary across developed and developing countries. Debt ratios in developing country firms are lower than those in developed country firms, largely due to the significantly smaller leverage ratios of firms in Muslim-majority countries. Although the debt ratios of DJIM firms are higher in "non-Muslim" countries, the set of firm-level capital structure determinants are not statistically explained by operating in a "Muslim" country. The study also documents that, before the global financial crisis of 2008, companies in developing countries have gradually become less leveraged worldwide. Originality/value This paper provides a new perspective into the differences between developed and developing country firms' capital structures by focusing on a relatively homogeneous data set restricted by leverage screening rules of an Islamic equity index and recognizing the Muslim-majority status of each firm's domicile country.
Keywords: G32; 330; Capital structure; Debt ratio; Islamic finance; Developed and developing countries